Assessing Novice Teams in Collaborative Software Engineering Education - Danang Wahyu Utomo; Egia Rosi Subhiyakto (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2016)
Novice teams is a group of novice student who had just taken software engineering course. Recent researches indicate that assessment approach can be used to improve knowledge and skill of student. The problem in assessment approach is “is assessment approach fair for level of student”?. In collaborative work, assessment is important to gain communication skill, experience, and most importantly promote responsibility. This study perform assessment approach for novice teams that applied in collaborative tool. The assessment approach consists of four components: attendance, discussion, assignment and contribution. In evaluation phase, the result indicate that the collaborative tool is support collaborative work and assessment approach is fair assessment for novice student. The respondent agree above 50% for each assessment component. Although, collaborative work still have the weakness such as collaborative tool only use one diagram.